2002
DOI: 10.1016/s1044-0305(02)00707-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and localization of the fatty acid modification in ghrelin by electron capture dissociation

Abstract: Electron capture dissociation (ECD) has been demonstrated to be an effective fragmentation technique for characterizing the site and structure of the fatty acid modification in ghrelin, a 28-residue growth-hormone-releasing peptide that has an unusual ester-linked n-octanoyl (C8:0) modification at Ser-3. ECD cleaves 21 of 23 possible backbone amine bonds, with the product ions (c and z⅐ ions) covering a greater amino acid sequence than those obtained by collisionally activated dissociation (CAD). Consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
(53 reference statements)
4
32
0
Order By: Relevance
“…Nearly all major peaks were accompanied by satellite peaks equivalent to water losses (and in some cases, two consecutive water losses), from both band y-ions, which complicated the spectrum severely. This behavior was also observed in SORI-CAD of the O-acylated polypeptide ghrelin [18]. The base peak in the SORI-CAD spectrum was the quadruply charged nonmodified polypeptide chain, corresponding to the loss of the full modification.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Nearly all major peaks were accompanied by satellite peaks equivalent to water losses (and in some cases, two consecutive water losses), from both band y-ions, which complicated the spectrum severely. This behavior was also observed in SORI-CAD of the O-acylated polypeptide ghrelin [18]. The base peak in the SORI-CAD spectrum was the quadruply charged nonmodified polypeptide chain, corresponding to the loss of the full modification.…”
Section: Resultssupporting
confidence: 56%
“…This loss corresponds to the incorporation of a hydrogen atom). In an equivalent study by Guan [18] of O-acylated polypeptides, a loss of the full fatty acid chain was observed as well. The second part of the modification that linked the palmitoyl moiety to the polypeptide chain was a glutamoyl residue, which was linked to the -amine group of lysine 26 through an amide bond (see Scheme 1).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…ECD of peptides with ester bonds has previously been investigated [36,37]. Marshall and co-workers have found that backbone cleavages in cyclic all-ester depsipeptides mainly occur in the O À C a bond [36], while Guan investigated fragmentation of the ester bond in a side chain [37].…”
Section: Introductionmentioning
confidence: 99%
“…(J Am Soc Mass Spectrom 2005, 16, 1060 -1066) © 2005 American Society for Mass Spectrometry E lectron capture dissociation (ECD) [1,2] is a relatively new MS/MS technique that has become popular because it provides better peptide and protein sequence coverage compared with other dissociation methods, and retains labile post-translational modifications (e.g., glycosylation [3,4] and phosphorylation [5][6][7][8]. Recent applications also include fatty acids [9], antibiotic/protein complexes [10], ubiquitination [11], oligonucleotides [12], and histones [13][14][15]. Despite its proven analytical utility, ECD suffers from limited conversion efficiency of precursor to product ions.…”
mentioning
confidence: 99%